Economic analysis of marsh gas development in countryside of China: A case study of Gongcheng County in Guangxi Province - Ting Cui; Chan Wang; Pu-yan Nie (Energy Reports, 2019)
Marsh gas is an important type of renewable energies and plays important role to solve the energy issue in remote countryside. This article captures the development of marsh gas in Gongcheng County of China with game theory model. Firstly, the development history of marsh gas in Gongcheng County is introduced. Secondly, the economic effects of all subsidy strategy are discussed. Subsidy to family marsh gas popularizes the marsh gas. Thirdly, whether to subsidize firms depends on transportation costs. Therefore, for the disperse residents, subsidy to family marsh gas seems more rational than that to firms. For concentrated residents, the conclusions are contrary.
Keywords: 330; Bioenergy; Countryside development; Energy; Forest; Gongcheng; Subsidy